IITA 50th Anniversary Conference - N2Africa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Towards Food and Nutrition Security for the next Half Century: Challenges, Opportunities, and Strategies. The International Institute of Tropical Agriculture (IITA) is 50 years old this year 2017. The year is therefore Golden Jubilee year for the institute, and is celebrated through two core events. The first event aimed at celebrating performance and achievements of the institute over its 50 years of operation. It also celebrated staff, alumni, partners and donors that have been part of the history and success of the institute to date. This celebration took place at IITA Headquarters in Ibadan, Nigeria, on 24 July 2017. Events were also held at the various regional Hubs of the institute (West, East, Central and Southern Africa). The Conference on Food and Nutrition Security Futures is the second core celebration event. It is designed to address various dimensions of the food and nutrition security challenge over the next 50 year cycle – leading to the centenary of IITA!! It seeks to leverage on the potential of science for the transformation of agriculture towards increased food security and economic development for African countries. This is pertinent particularly given the challenge of population growth and climate change. It is estimated that the population of the world would reach 9 billion by the year 2050. Food availability in quantity and quality would be a major challenge for feeding this number of people. Climate change with its direct and indirect consequences places further challenge on this scenario.